Acute effects of Kinesio taping on muscle strength and fatigue in the forearm of tennis players - Zhang, S.; Fu, W.; Pan, J.; Wang, L.; Xia, R.; Liu, Y. (Journal of Science and Medicine in Sport, 2016)
Objectives: To explore the immediate effects of Kinesio taping applied over the wrist extensors and flexors on muscle strength and endurance during isometric and isokinetic muscle actions. Design: The study had a single-blinded, placebo control, and randomized design. Methods: Fourteen trained male volunteers were required to complete 5 s isometric maximal voluntary contractions and 50 consecutive maximal concentric wrist extension and flexion repetitions at each of two angular speeds (60°/s and 210°/s) in three taping conditions: Kinesio taping (KT), placebo taping (PT), and no taping (NT). Results: KT did not improve peak moment, peak power, average power, and total work for wrist extensors and flexors in the isometric and isokinetic contractions. However, KT showed a 13% decrease in work fatigue of the wrist flexors compare to NT (p = 0.014) at 60°/s. Furthermore, a 20% decrease was also observed in the rate of decline of moment (k) of the wrist flexors in KT compared to NT (p = 0.007), and the k in PT was also significantly lower in magnitude compared to NT (p = 0.035). Moreover, there was also a trend in terms of magnitudes for kKT < kPT < kNT in the wrist flexors at 210°/s. Conclusions: Kinesio taping may not be able to modulate strength production in healthy athletes immediately, but does have a significant positive effect on reducing muscle fatigue during repeated concentric muscle actions. Additionally, the potential beneficial effects of placebo taping on muscle endurance should not be ignored either.